2017
DOI: 10.1080/19012276.2016.1270774
|View full text |Cite
|
Sign up to set email alerts
|

The perception of the poor: Capturing stereotype content with different measures

Abstract: Even though Sweden stands out in many ways, with for example a well-developed welfare system, there are some indications that Swedish egalitarianism does not include tolerance for people with low income. The present research concerns the content of the Swedish stereotype of poor people, and examines whether the poor are associated with just as negative traits as they are in other countries. Three different measurement methods were employed to investigate the contents and strength of the stereotype. In Study 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 49 publications
2
35
1
2
Order By: Relevance
“…Our model implies one reason why negative stereotypes of the poor may be so prevalent (Brantlinger, 2003; Darley & Gross, 1983; Durante et al, 2017; Lindqvist, Björklund, & Bäckström, 2017; Lott & Saxon, 2002; C. K. Miller et al, 1968) and why some commentators attribute the vicious cycle of status to class-based differences in work ethic (Cozzarelli et al, 2001; Iyengar, 1996; Lepianka, Gelissen, & van Oorschot, 2010; Pew Research Center, 2014; Smith & Stone, 1989; Zucker & Weiner, 1993).…”
Section: Practical Meaning: the Psychology Of Low Statusmentioning
confidence: 93%
“…Our model implies one reason why negative stereotypes of the poor may be so prevalent (Brantlinger, 2003; Darley & Gross, 1983; Durante et al, 2017; Lindqvist, Björklund, & Bäckström, 2017; Lott & Saxon, 2002; C. K. Miller et al, 1968) and why some commentators attribute the vicious cycle of status to class-based differences in work ethic (Cozzarelli et al, 2001; Iyengar, 1996; Lepianka, Gelissen, & van Oorschot, 2010; Pew Research Center, 2014; Smith & Stone, 1989; Zucker & Weiner, 1993).…”
Section: Practical Meaning: the Psychology Of Low Statusmentioning
confidence: 93%
“…In the United Kingdom, for example, several popular television programs have portrayed families on low incomes or benefits as being lazy and lacking motivation to engage in economic activity (Augoustinos & Callaghan, 2019; Jones, 2016). One Swedish study found that respondents described the stereotypes about “poor citizens” using terms such as “lazy,” “uneducated,” “unintelligent,” “dishonest,” and “work‐shy” (Lindqvist, Björklund, & Bäckström, 2017). Moreover, Shutts and colleagues (2016) found that children as young as four in the United States expected children who were portrayed as wealthy to be more popular and to be less likely to make a mistake in a coloring task than those who were portrayed as poor.…”
Section: The Identities In Context Model: Linking Contextual Variatiomentioning
confidence: 99%
“…Rich people, as a salient societal group, are cross-nationally (37 samples in 27 nations) stereotyped as more competent (but colder) than poor people, especially under conditions of greater income inequality [5]. In contrast, poor people are stereotyped as lazy and substance abusers in the US [6] as well as in the egalitarian Sweden [7]. Cross-nationally, poor people are perceived as incompetent (even more so in unequal societies) [5, but see also 7], and judged as animal-like in the UK, US, and Australia [8*].…”
Section: Social-class Stereotype Contentmentioning
confidence: 99%
“…In contrast, poor people are stereotyped as lazy and substance abusers in the US [6] as well as in the egalitarian Sweden [7]. Cross-nationally, poor people are perceived as incompetent (even more so in unequal societies) [5, but see also 7], and judged as animal-like in the UK, US, and Australia [8*]. Low-status (e.g., blue-collar or working-class) workers share a similar stereotype: They are cross-nationally perceived as incompetent (but sometimes warm, depending on the country; see [9]), and they are dehumanized (either as animals or interchangeable objects) [10].…”
Section: Social-class Stereotype Contentmentioning
confidence: 99%